Asuhan Keperawatan Keluarga Tn. B dengan Masalah Utama Gout Artritis (Asam Urat) pada Tn. B di Jamur RT 02 RW VII, Trangsan, di Wilayah Puskesmas Gatak, Sukoharjo - Herlambang, Ikhsan Probo, Agustaria Budinugroho S. kep., Ns (2013)
Background: Gout Artritis is a disease caused by a metabolic disorder of uric acid in the body that cause hyperuricemia or uric acid levels in the blood of excess. Methods: The authors collected data by the method autoanamnesa (ask for sick family members), alloanamnesa (asking the family or significant others), participatory observation that direct observation of all family members and perform a physical examination. Result: After the action during the four day nursing care, diagnosis emerges is a high risk of joint pain and movement disorders. In accordance with the implementation of the action plan has been established. Conclusion: After starting a family nursing care action 1-4 may 2013 with Gout Artritis problems, the authors are able to perform better nursing care ranging from assesment, to determine nursing diagnosis, planning, implementation and evaluation.